Analisis Hubungan Stres Kerja, Kepuasan Kerja,Dan Komitmen Organisasi Terhadap TurnoverIntention Karyawan Pt TelekomunikasiIndonesia Tbk Witel Solo - Wahyuni, Sri; , Ihwan Susila S.E., M.Si., Ph.D (2017)
The purpose of this study is to analyze the effect of work stress, job satisfaction,and organizational commitment on turnover intention. The population of thisresearch is the employees of PT Telekomunikasi Indonesia Tbk Witel Solo. The study used 65 employee with multiple regression analysis as the analyticalmethod. The result showed that work stress has significantly positive affect onturnover intention, and organizational commitment has significantly negativeaffect on turnover intention. Meanwhile, job satisfaction do ot affect on turnoverintention. The result of the coefficient of determination ( obtained R square of0,373. This result showed that turnover intention can be explained by the variablework stres, jo satisfaction, and organizational commitment of 37,3%, meanwhile62,7% are influenced by ather factors outside variables research.